Features and essence of the legal process - D. Chulyukin, Lev (2018)
The paper considers the problem of understanding the legal process. The modern procedural legislation is analyzed for the existence of a legal process definition. The complexity and multifacetedness of the legal process manifestation was noted. The authors analyzed the current state of the problem on determining the essence of the legal process. The scientific works of Russian and foreign scientists devoted to the study of the nature of the legal process have been studied. Traditional (narrow) and universal (wide) scientific approaches to understanding the object of research are noted. The analysis of the legal process features identified in the legal science is carried out. The paper takes into account the legal science achievements and the peculiarities of the procedural and legal activity, on the basis of which the authors updated the idea of the modern legal process. As a result of the work, the main features of the legal process are identified, and its essence is determined. The essence of the legal process is presented as a system of basic features that give it a qualitative certainty. A study of this problem was conducted to establish a unified approach to understanding the legal process that ensures the unambiguity and certainty of the concept used. It is necessary to introduce into the procedural legislation its official definition with a view to eliminating in the practical activity the confusion of the legal process with related phenomena of legal reality: a jurisdictional process, a judicial process, and legal proceedings.